Quercetin 3, 7, 3´, 4´-Tetrasulphate from Flaveria bidentis Inhibits the Plasminogen Activator Inhibitor-1 but not the Tissue-Type Plasminogen Activator Expression in Human Normal Fibroblasts - Guglielmone, Hugo (2015)
Sulphated flavonoids quercetin 3, 7, 3´, 4´-tetrasulphated (QTS) and quercetin 3-acetyl-7, 3´, 4´-trisulphate (ATS), obtained from Flaveria bidentis have demonstrated some antithrombotic properties. We analyzed whether both compounds affected the expression of tissue-plasminogen activator (tPA) and plasminogen activator inhibitor-1 (PAI-1), the components of the fibrinolytic system. Normal human fibroblasts were pretreated with different concentrations of each sulphated flavonoid (0.1 μM to 500 μM), during 2 and 3 h followed by a 24 h incubation with phorbol myristate acetate (PMA). Results of the tPA and PAI-1 expression compared to control, showed different behaviors for the two flavonoids studied. A null inhibitory effect on the tPA expression was detected at all the concentrations for QTS and ATS. In contrast, QTS from 50 μM onwards showed a significant inhibitory effect on PAI-1 expression (p< 0.05). The profibrinolytic activity of QTS enhances its antithrombotic properties and encourages us to study these properties in animal models.